Membangun Karakter Peduli Lingkungan Melalui Prinsip Kebersihan - Rif'ah, Rif'ah (Jurnal Pendidikan Islam Indonesia, 2020)
Keeping the environment clean is an Islamic teaching. The purpose of this research is to describe and analyze the efforts of building awarness about environmental cleanliness and to reveal the parties involved in it. The data was collected through interviews with madrasah principals, teachers and students, observation and documentation. The results of the study are: 1) Building the awarness of caring for environmental cleanliness is done through: maintaining cleanliness and purity of the classroom, maintaining the cleanliness and neatness of the yard, one student program one garbage and tidying sandals. The parties involved in building the awarness for caring environmental cleaniness are all elements in the madrasa, the principal, homeroom teacher, teacher and all students.